International trade and uneven distribution of income - Hakhverdyan, David Nersik; Pakhlyan, Anna Armen (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2019)
The turbulent events of the last quarter of the 20th century (the collapse of the socialist system and the transition of the post-socialist countries to a market economy, China’s accession to the world market and the successive trends of trade liberalization in a number of countries) do not doubt that trade and technology play an important role in changing the structure of production and wages throughout the world. At the beginning of the 20th century globalization tendencies were transformed into a deglobalization. This was partially due to the fact that growth of international trade did not properly contribute to the welfare of people and the mitigation of income polarization as it was expected to. Although, there is no doubt that trade and technology have played an important role in the change of production structure and salaries around the world. The subject of research in the article are the main causes and consequences of the polarization of income in the world economy. The purpose of the study is to identify the impact of the growth of international trade on human well-being and reduction of income polarization.The main objective of the study is to analyze the dynamics of income distribution in the world in the context of the expansion of international trade. The article uses general scientific methods: system analysis - to determine the features of the development of international trade, a method of scientific abstraction that allows to present the general nature of the uneven distribution of income in the world economy and to make assumptions about the expected future through extrapolating data. Results: Based on the analysis of the dynamics of the change in the basic indicators of income distribution, the problem aspects of the impact of international trade on the polarization of the world population’s incomes are revealed.Conclusion:According to studies,economic growth rates deepened inequality between countries, as some have learned to benefit from new opportunities better than others. Moreover, it turned out that trade is affecting the labor market disproportionately even within one country.